GAMBARAN STATUS PERIODONTAL PADA PASIEN SINUSITIS (KAJIAN DI POLIKLINIK THT RUMAH SAKIT UMUM MEURAXA) - Sunnati .; Sri Rezeki; Zulfan M. Alibasyah; Dewi Saputri; Syifa . (Journal of Syiah Kuala Dentistry Society, 2019)
Sinusitis is an inflammation of nose and paranasal sinuses. Signs and symptoms that found in sinusitis patients are problem in sense of smell, facial pain, nasal obstruction, and discharge of mucopurulentnasal drip. Nasal obstruction tend to causes patient mouth breathing then patient having symptom ofxerostomia. In xerostomia patient which accompanied by decrease of salivary flow rate, theantimicrobial action of saliva will decrease, so the formation of plaque will increase. This study aimsto determine periodontal status of sinusitis patients. This research is a descriptive study with nonexperimental design. The method used to select the subject is purposive sampling, which the subjectsare sinusitis outpatients in Ear, Nose, Throat Polyclinic of Meuraxa Hospital. This research startedfrom August to October 2019 in Meuraxa Hospital, Banda Aceh. Research done by the examination ofOHIS, pocket periodontal depth, and clinical attachment loss. The results show that subjects with acutesinusitis are 24% and chronic sinusitis are 76%. Oral hygiene of sinusitis patients show 72% fair scoreand 28% poor score. Periodontal pocket depth under 4 mm in percentage of 100%. Clinical attachmentloss show 88% mild, 8% fair, and 4% severe. The conclusion of this study are no sinusitis patienthaving good oral hygiene, but the higher score is fair oral hygiene with percentage of 72%. Periodontalpocket depth in all subjects are under 4 mm. Mild clinical attachment loss is the greater with percentageof 88%.Keywords: Sinusitis, oral hygiene, periodontal pocket, clinical attachment loss